Ethnoveterinary study of medicinal plants used for cattle treatment in Bojonegoro District, East Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pratama AM, Herawati O, Nabila AN, Belinda TA, Wijayanti AD. 2021. Ethnoveterinary study of medicinal plants used for cattle treatment in Bojonegoro District, East Java, Indonesia. Biodiversitas 22: 4236-4245. Bojonegoro is a rural district in Indonesia's East Java Province where farming and cattle rearing are the main economic activities. The Bojonegoro District's cattle producers employ some medicinal plants specifically for the treatment of bovine illnesses. However, no data has been reported thus far. The goal of this research was to find and document ethnoveterinary medicinal herbs for cattle cures in the Bojonegoro District. A total of 41 cattle breeders were interviewed for the study. To collect demographic and ethnoveterinary medicinal plant data, each informant was interviewed using a semi-structured questionnaire in the native language of each informant. The stastitical analysis in this study include informant consensus (Fic), Fidelity Level (FL), and Plant Part Frequency (PPF). Approximately 78.00% of the respondents are between the ages of 30 and 50, with 36.59% having only graduated from senior high school. The Peranakan Ongole (PO) is the most common breed preserved by cattle breeders. In the study area, 41 ethnoveterinary medicinal plants were mentioned by male respondents to cure cattle health problems. Digestive illnesses are the most frequent ailments in cattle treated with medicinal plants. Curcuma longa L. was the most commonly mentioned medicinal plant. A majority of the source ethnoveterinary medicinal plants were cultivated on-site and the leaves of these plants were most often used.
Keywords: Bojonegoro, Cattle, Cattle Breeders, Ethnoveterinary, Medicinal plants